The Impact of Various Physiotherapy Programs on Static and Dynamic Balance for Patients after Stroke (Baltic Journal of Sport and Health Sciences, 2018)
Background. The imbalance in many scientifc sources is described as a major disorder in patients with a history of stroke. Often, the importance or disruption of torso control is also indicated on balance impairments. We believe that both physiotherapy programs will have impact on balance however better results on balance tests will be in group which balance training composed of unstable planes. Research aim was to measure impact of various physiotherapy programs on static and dynamic balance for patients after stroke. Methods. To evaluate changes of static and dynamic balance we used: Berg balance test, Tinetti test, PASS test, dynamic gait index, trunk impairment scale, special STREAM movements test for patients after stroke, Mini balance evaluation test for patients after stroke. Training methods of balance were for two diﬀerent physiotherapy programs: intervention group (basic physiotherapy program with exercises on unstable planes) and control group (basic physiotherapy program with gait training elements). Results. When evaluating balance, results in both groups were almost equal, which shows that balance was disturbed and there was a huge risk of falls, moreover all patients walked with aid measures. At the beginning of rehabilitation, the average of all balance evaluating tests in both groups scored 16.92 and 15.05. All results were statistically signifcant (p < .05). At the end of research, variations between all test results were defned statistically signifcant. Repeatedly evaluating results of both groups at the end of rehabilitation, all test averages were improved: at the beginning, the intervention group average score was 16.92 and after rehabilitation, it was 34.79. For control group results, the average score of all tests was 15.05 and at the end it was 31.90. Summing up, it was established that in both groups balance in rehabilitation period improved. Conclusions. Physiotherapy programs based on exercises on unstable planes or gait training elements improve balance for patients after stroke. Many studies have confrmed the hypothesis of our study that using unstable planes or walking training methods improve balance, but for a statistically signifcant change in improving the balance, it will be necessary to use unstable planes.Keywords: physical therapy, stroke, balance, static, dynamic.